A companion to angels in medieval philosophy - Hofffmann, Tobias (Leiden ; Boston : Brill, 2012)
While Christian theologians have always been greatly interested in angels, during the course of the thirteenth century their treatments of angelology became increasingly motivated by philosophical concerns. Many of the most original and ingenious contributions of medieval philosophy came to light in the context of angelology, for angelology provided an ideal context for discussing issues such as the structure of the universe, the metaphysical texture of creatures, and theories of time, knowledge, freedom, and linguistics. This volume centers on the period from Bonaventure to Ockham while also discussing some original positions by earlier thinkers such as Augustine and Anselm of Canterbury. Its nine thorough studies bring to light some neglected but highly fascinating aspects of medieval philosophy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Angels -- History of doctrines -- Middle Ages, 600-1500.; Angels; Philosophy, Medieval; RELIGION / Christian Theology / Angelology & Demonology; Electronic books